ANALISIS PENGARUH KUALITAS MAKANAN, KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN, LINGKUNGAN FISIK SEBAGAI VARIABEL MEDIASI STUDY KASUS BALE AYU RESTO GIWANGAN YOGYAKARTA - Pratama, Fauzi; Wikaningtyas, Suci Utami (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
Analysis of the effect of food quality, service quality on customer satisfaction. This study aims to analyse the effect of food quality, service quality on customer satisfaction with the physical environment as a mediating variable at Bale Ayu Resto Giwangan Yogyakarta. Using a quantitative approach, data was collected through questionnaires from 100 customers, analysed using partial least square (PLS) The results of this study show: food quality has a positive effect on customer satisfaction , food quality has a positive effect on the physical environment, service quality has a positive effect on customer satisfaction, service quality has a positive effect on the physical environment, the physical environment has no direct effect on customer satisfaction, food quality does not mediate the physical environment through customer satisfaction, service quality does not mediate the physical environment through customer satisfaction.